THE CORRELATION BETWEEN MECHANICS VIBRATION OF GRINDER MACHINE AND CARPAL TUNNEL SYNDROME CASE FOR WELDING WORKER AT DENPASAR - Pandiangan, Grace; Wibawa, Ari; Adiputra, Indah; Adiatmika, I Putu Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 1 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i01.p01, 2018)
ABSTRACT The objective of this research is to know the correlation between the mechanic vibration of grinder and the complaints of Carpal Tunnel Syndrome from the welding workers in Denpasar. This research is an observational analytic cross sectional purposive sampling research with 95 respondents. The grinding machine vibration is measured using vibrationmeter and the CTS complaint is measured using Phalen test. From this research, the result of p = 0,007 < ? = 0,05 with the chi square test that shows a significant link between the mechanic vibration and the CTS complaints. The strength of the link is tested with spearman rho, the result of r = 0,313 which is quite strong. The conclusion of this research is derived firm the causality of mechanical vibration from grinding machine with the complaints of CTS on welding worker in Denpasar.   Keyword : mechanic vibrations, grinding machine, welding, carpal tunnel syndrome